PENYELESAIAN SENGKETA PROSES PEMILU DI BAWASLU PROVINSI KALIMANTAN TENGAH DALAM PERSPEKTIF KEADILAN - Rudyanti Dorotea Tobing (Fakultas Hukum Universitas PGRI Palangkaraya, 2019)
Elections are an important instrument in every democratic country that adopts a system of representation. Elections are conceptually a means of implementing people's sovereignty. The 2019 elections were held based on Law Number 7 of 2017 concerning General Elections. Basically, the Election Law accommodates the interests of all parties in resolving disputes in the electoral process. In the Election Law the duties and functions of Bawaslu, Provincial Bawaslu and Regency / City Bawaslu are strengthened and clarified. One of them is given the duties and authority related to the election process dispute resolution. Article 466 of the Election Law states that: Election Process Disputes include disputes between Election Contestants and Election Contest participants and Election Organizers as a result of the issuance of KPU Decisions, Provincial KPU Decisions and Regency / City KPU Decisions. During the 2019 elections from the first to the last stage, Bawaslu has received 10 (ten) Requests for Election Process Dispute Resolution, which are spread in several districts in Central Kalimantan Province. Central Kalimantan Bawaslu and Regency / City Bawaslu have exercised their authority to prevent election process disputes and resolve election process disputes by being fair and in accordance with laws and regulations. So that justice in the administration of elections can be felt both by Election Contestants and Election Organizers in Central Kalimantan Province.